Dreamm-2: single-agent belantamab mafodotin in patients with relapsed/refractory multiple myeloma (rrmm), including subgroups with renal impairment (ri) and high-risk (hr) cytogenetics - S. Lonial; H.C. Lee; A. Badros; S. Trudel; A.K. Nooka; A. Chari; A-O. Abdallah; N.S. Callander; D.W. Sborov; A. Suvannasankha; K. Weisel; P.M. Voorhees; et al. (Hematology Reports, 2020)
Introduction: Belanatamab mafodotin (GSK2857916; belamaf; BLENREP) showed deep and durable single-agent activity in the pivotal DREAMM-2 study primary analysis (NCT03525678)(1–5) in a patient population that historically has a poor prognosis (overall survival [OS] 6–9 months). This study aims to present longer-term efficacy/safety outcomes (13-month follow-up) with single-agent belamaf in DREAMM-2 in the overall patient population and patients with HR cytogenetics and RI, subgroups with poor outcomes. Methods: DREAMM-2 is an ongoing study of belamaf 2.5 mg/kg (n=97) or 3.4 mg/kg (n=99). Primary outcome: overall response rate (ORR; ≥partial response). In post-hoc analyses, HR-cytogenetics included t(4;14), t(14;16), 17p13del, or 1q21+. RI was based on estimated glomerular filtration rate (mild: ≥60–<90 mL/min/1.73 m[2]; moderate: ≥30–<60 mL/min/1.73 m[2]). Results: Overall population ORRs in the 2.5-mg/kg and 3.4-mg/kg groups were 32% (97.5% CI: 21.7–43.6) and 35% (97.5% CI: 24.8–47.0); 19% and 23% of patients (58% and 66% of responders) achieved very good partial response or better. Median duration of response was 11.0 (95% CI: 4.2–not reached [NR]) and 6.2 months (95% CI: 4.8–NR). Median progression-free survival was 2.8 (95% CI: 1.6–3.6) and 3.9 months (95% CI: 2.0–5.8); median estimated OS was 13.7 (95% CI: 9.9–NR) and 13.8 months (95% CI: 10.0–NR). Most common Grade ≥3 adverse events (AEs) were keratopathy (microcyst-like epithelial changes [MECs] observed on eye examination; 2.5 mg/kg: 46%; 3.4 mg/kg: 42%), thrombocytopenia (2.5 mg/kg: 22%; 3.4 mg/kg: 32%), and anaemia (2.5 mg/kg: 21%; 3.4 mg/kg: 27%). AE-related permanent discontinuation occurred in 9% and 12%; discontinuation due to MECs was rare (2.5 mg/kg: 1%; 3.4 mg/kg: 3%). HR cytogenetics and RI subgroup analyses will be presented at the conference. Conclusions: Deep and durable responses to single-agent belamaf were sustained and no new safety signals identified with longer follow-up in this heavily pretreated RRMM population. Funding: GSK (205678). Drug linker technology licensed from Seattle Genetics; monoclonal antibody produced using POTELLIGENT Technology licensed from BioWa. Encore Statement: ©2020 Society of Hematologic Oncology, Inc. Reused with permission. This abstract was accepted and previously presented at the 2020 SOHO Annual Meeting. All rights reserved. 1. Lonial et al. Lancet Oncol. 2020; 2. Lonial et al. ASCO 2020. EP436; 3. Cohen et al. ASCO 2020. EP441; 4. Trudel et al. EHA 2020. EP1037; 5. Lee et al. ASCO 2020. EP419